The social construction of fasting exemptions among manual laborers from the perspective of the sociology of religion - Az Zahro, Zainab Fatimah (Maliki Interdisciplinary Journal, 2026)
This study discusses heavy workers’ understanding of fasting rukhsah from the perspective of the sociology of religion. Islam provides rukhsah as a form of relief for individuals facing difficulties in performing fasting, including those engaged in physically demanding work. However, heavy workers show different views regarding the use of rukhsah. Some perceive it as a manifestation of compassion and flexibility in Islamic law, while others continue fasting as a form of faithfulness and patience. This study uses a descriptive qualitative method with a library research approach through the analysis of Qur’anic verses, theories of sociology of religion, and related literature. The findings reveal that workers’ understanding of fasting rukhsah is influenced not only by religious knowledge but also by social environment, work culture, family background, and religious leaders’ perspectives. Peter L. Berger and Thomas Luckmann’s social construction theory explains that religious understanding is formed through social interaction in everyday life. Therefore, differences in understanding fasting rukhsah should be addressed with mutual respect without negative judgment toward others’ religious practices.